Pemetaan Lahan Sawah Berbasis Sistem Informasi Geografis di Subak Petangan dan Subak Pakel II, Desa Ubung Kaja, Kecamatan Denpasar Utara - SIRAIT, DANIEL VALENTINO; ADI, I GUSTI PUTU RATNA; BHAYUNAGIRI, IDA BAGUS PUTU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.10, No.1, Januari 2021, 2021)
Mapping of Subak Rice Fields Based on Geographical Information Systems in Petangan Subak and Pakel II Subak  in  Ubung Kaja Village, North Denpasar District Subak Petangan and Subak Pakel II are rice fields that have the potential to experience land use change. Based on data from the Central Statistics Agency (BPS) of Bali Province in 2017, the area of ??rice fields in Denpasar City has decreased by an average of 31.86 ha/year or decreased by around 1.28% per year. It is feared that it will experience a decline in the next 5 years. To anticipate further land use changes, a Regional Regulation (Perda) is required for the Protection of Subak Land as an LP2B Area, and is set forth in a Detailed Spatial Plan (RDTR). The purposes of research: knowing the area of ??subak Petangan and Subak Pakel II rice fields, knowing the subak designated in the RTHK area, making a GIS based information database on the potential of subak. According to the RTRW for the City of Denpasar (2011-2031), RTHK in urban areas is at least 30% of the city area. The area of ??Subak Pakel II which is in the RTHK of Denpasar City is 28.3 ha and is designated as a sustainable subak. Based on this, it is necessary to carry out a mapping of paddy fields in Subak Petangan and Subak Pakel II so as to facilitate planning, implementation, monitoring and evaluation of LP2B. The digitization results show that the area of ??Subak Pakel II is 49 ha, while the area of ??Subak Petangan is 36 ha. The area of ??subak rice fields in the RTHK area is 35.6 ha, namely in Subak Pakel II. The area of ??subak non-rice fields in Subak Pakel II is 7.3 ha. Subak land area that is not in the RTHK area is in Subak Pakel II, which is 21 ha.